KEPUASAN MASYARAKAT ACEH BARAT TERHADAP PELAYANAN PEMBUATAN JKN PADA BPJS KESEHATAN CABANG MEULABOH - Ummul Zulfa; Alfian Anas (Warmadewa Management and Business Journal (WMBJ), 2022)
This study aims to analyze whether the people of Aceh Barat are satisfied with the services in making JKN provided by BPJS Kesehatan Meulaboh Branch, and whether the services provided by BPJS Kesehatan are as expected by the community. The study used descriptive qualitative data. The population in this study were all participants in making JKN cards with a total sample of 100 people. It can be seen from the highest score on the suitability of the service with what is expected to be in the good category with an average value of 2.97. Then the second highest average value where reliability and assurance is 2.96. Third, the lowest value is in tangible and empathy of 2.92. This value can indicate that the satisfaction of the people of West Aceh at BPJS Kesehatan Meulaboh Branch is good.